Adopsi Informasi Produk Skincare dan Kosmetik di YouTube: Peran Pengaruh Informasional Pada Ulasan - Katarina Rosyantika Sinaga; Ira Siti Sarah (Politeknik Negeri Bengkalis, 2020)
Consumers are being more digital-natives. More consumers are using online reviews made by others to find out information before deciding to buy a product, especially for skincare and cosmetic products. However, there is little to none study focuses on the information adoption of skincare and cosmetic consumers. This study aims to test the role of the informational influence of skincare and cosmetic product reviews on information adoption on YouTube. The purposive sampling was used in the sampling collection technique. An online questionnaire was distributed to 385 respondents who have watched skincare or cosmetic product reviews on YouTube. This research finds that the adoption of information on YouTube was significantly affected by the informational influence of product reviews by 23.1%.